Multi-level explosion risk analysis (MLERA) for accidental gas explosion events in super-large FLNG facilities - Huang, Y.; Ma, G.; Li, Jingde (Elsevier, 2017)
© 2016 Elsevier Ltd When assessing explosion risks of super-large offshore structures such as Floating Liquefied Natural Gas (FLNG) facilities, there are neither design rules nor industry standards available as FLNG is a new technology. Meanwhile, a large amount of Computational Fluid Dynamic (CFD) calculation time is required due to its super-large size and highly complicated topside structures. A multi-level explosion risk analysis method (MLERA) is developed in this paper, which divides the whole structure into subsections and applies detailed CFD calculations only to the areas with the highest level of potential risks so that the computational time can be reduced to a realistic and acceptable level. The MLERA includes three levels, which are qualitative risk screening, semi-quantitative risk classification, and quantitative risk assessment. A CFD tool called FLACS is used as a calculation tool for detailed risk quantification, and an ALARP (as low as reasonably practical) method is selected as a calibration tool and used to determine the acceptance of the explosion risk. Meanwhile, since the current design standards for normal offshore platforms are not sufficient for super-large structures, during the risk screening and risk classification processes, safety barriers are used as extra risk indicators in addition to the traditional ones. A case study is conducted based on a cylindrical FLNG model, and the result of the case study proves that the proposed MLERA method is able to save a large amount of computational time.